Antimicrobial Peptides sebagai Obat Alternatif pada Resistensi Antibiotik - Fitri, Nyoman (Jurnal Kefarmasian Indonesia, 2012)
Antibiotic resistance has become a global public-health problem, thus it is imperative that new antibiotics have to be developed continously. Antimicrobial peptides (AMPs) are component of the innate immune response, which is the principal defence system for the majority of living organisms. Similar to antibiotics, most AMPs have a broad antimicrobial spectrum and highly active against fungi. AMPs are known to have interaction with biomembranes to lyse microbial cells. Many researches have tried to develop AMPs as future drugs for antibiotic resistance. Many AMPs also possess antiviral or anti-parasite activity. However, antimicrobial peptides have their own disadvantages. We review the role of these molecules in human’s health, their advantages and disadvantages as alternative antimicrobial for antibiotic resistance.